A Comparative Study Of Aarom Exercise With Icing And Aarom Exercise With Prolonged Stretching To Reduce Spasticity In Spastic Cerebral Palsy - Vanshika; Dr. Monika Sharma (Revista Electronica de Veterinaria, 2024)
Introduction-Increased muscular tone and resistance to movement, which restrictsfunctional mobility and independence, are hallmarks of spastic cerebral palsy (CP). The goals of several therapy approaches are to lessen stiffness and enhance motor results in people with spastic cerebral palsy. The effectiveness of Active-Assisted Range of Motion (AAROM) exercises combined with icing versus AAROM exercises paired with extended stretching in reducing spasticity in patients with spastic cerebral palsy is examined in this study.Objectives of the Study:The objectives of this comparative study is to find out the effectiveness between the two intervention groups (AAROM with icing vs. AAROM with prolonged stretching) on muscle tone, joint flexibility, and spasticity reduction in calf region using the MAS,ROM,VAS.Method: The research here is purely experimental. According to the study's inclusion and exclusion criteria, a total of 30 individuals were included, with the age range ranging from 5 to 15 years. The participants were split into two groups. One group was given AAROM exercises with ice, while the other group received AAROM activities with extended stretching for plantarflexors. Both groups were given these exercises three times a week for 45 minutes, and the results were measured after six weeks. Pre- and post-treatment assessments were conducted using ROM, MAS, and VAS. Result: We used paired and unpaired t-tests as well as an independent t-test for ROM, MAS, and VAS to examine the results. Both groups experience notable improvements, however the control group (GROUP B) that underwent AAROM exercise with extended stretching showed even more remarkable improvements in the value of the outcome measures (MAS score and VAS score) than the experimental group.Conclusion: This study concludes that both the protocol reduces reduces pain, discomfort, improve mobility and reduces spasticity.But the results suggest that AAROM exercises with prolonged stretching is a more sustainable approach for managing spasticity and have given better effects than Group A.